Reconstructing Islamic Political Epistemology for Modern Governance - Febry Suprapto; Babussalam; Heri Rifhan Halili (PT. Education Research Center, 2025)
The growing complexity of contemporary governance has renewed scholarly interest in reconstructing Islamic political thought as a normative framework for modern political and administrative challenges. Although previous studies have widely discussed Islamic governance, maqāṣid al-sharī‘ah, and political reform, limited attention has been given to reconstructing the epistemological foundations of classical Islamic political thought into an integrated model for contemporary governance. This study aims to reconstruct those foundations and examine their contribution to accountable, participatory, and ethical governance in Muslim societies. Using qualitative library research with historical-philosophical and conceptual approaches, this study analyzes classical Islamic political literature and contemporary scholarship through documentary research. Data were examined using qualitative content analysis, thematic analysis, and constant comparative analysis. The findings show that Islamic political epistemology is built upon six interconnected sources of knowledge: the Qur’an, Sunnah, ijmā‘, qiyās, ijtihād, and maqāṣid al-sharī‘ah. These principles can be transformed into a governance-oriented framework emphasizing accountability, participation, ethical leadership, transparency, and public welfare. The study argues that contemporary Islamic political epistemology is a dynamic knowledge system capable of integrating Islamic intellectual heritage with modern governance principles. Its novelty lies in proposing an integrated epistemological model that bridges classical Islamic political thought and contemporary governance theory.